2013
DOI: 10.1161/hypertensionaha.113.01337
|View full text |Cite
|
Sign up to set email alerts
|

Diminazene Aceturate Enhances Angiotensin-Converting Enzyme 2 Activity and Attenuates Ischemia-Induced Cardiac Pathophysiology

Abstract: Angiotensin-converting enzyme 2 (ACE2) plays a critical role against myocardial infarction (MI). We hypothesized that activation of intrinsic ACE2 would be protective against ischemia-induced cardiac pathophysiology. Diminazine aceturate (DIZE), a small molecule ACE2 activator has been used to evaluate this hypothesis. DIZE (15 mg/kg/day, s.c.) was injected two days prior to MI surgery and continued throughout the study-period. MI rats showed a 62% decrease in fractional shortening (FS,%) [control (Con): 51.1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
134
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(140 citation statements)
references
References 34 publications
5
134
1
Order By: Relevance
“…Our study provides the first experimental evidence that DIZE can activate ACE2 and such activation plays an anti-inflammatory role in ocular inflammation model. Moreover, previous studies have demonstrated that DIZE activates ACE2 and the beneficial effects by DIZE are abolished by ACE2/Ang-(1-7)/Mas antagonists, 26,28,45 suggesting that these beneficial effects are mediated by activating the ACE2/Ang-(1-7)/Mas axis. In fact the antiinflammatory effects of DIZE in most recent studies 43,46 may also involve the ACE2/Ang-(1-7)/Mas axis, since Ang IImediated signaling is known to activate MAPK and the NF-jB signaling pathway.…”
Section: Discussionmentioning
confidence: 92%
“…Our study provides the first experimental evidence that DIZE can activate ACE2 and such activation plays an anti-inflammatory role in ocular inflammation model. Moreover, previous studies have demonstrated that DIZE activates ACE2 and the beneficial effects by DIZE are abolished by ACE2/Ang-(1-7)/Mas antagonists, 26,28,45 suggesting that these beneficial effects are mediated by activating the ACE2/Ang-(1-7)/Mas axis. In fact the antiinflammatory effects of DIZE in most recent studies 43,46 may also involve the ACE2/Ang-(1-7)/Mas axis, since Ang IImediated signaling is known to activate MAPK and the NF-jB signaling pathway.…”
Section: Discussionmentioning
confidence: 92%
“…Recently, ACE2 priming by the pharmacological activator, xanthenone (XNT), has been shown to protect the function of endothelial progenitor cells in hypertension and diabetes (5,11,18,23). In the present study, we have used a newly discovered ACE2 activator, DIZE (20,40,46), and shown that it enhances ACE2 activity in vitro. Chronic DIZE treatment elevated the activity of local vascular ACE2, subsequently increased the production of Ang (1-7), and augmented both EDRs in conduit aortas and FMD in resistance arteries from db/db mice.…”
Section: Discussionmentioning
confidence: 96%
“…Chronic treatment with DIZE ameliorated the extent of pulmonary hypertensin and fibrosis, renal tissue injury, and myocardial infarction consistent with enhanced levels of Ang-(1-7) and a reduction in Ang II [84,[87][88][89][90]. Interestingly, DIZE treatment was also associated with increased mRNA levels of ACE2 suggesting that DIZE may exhibit actions apart from the direct activation of the peptidase [87,91]. However, it should be noted that the effects of DIZE on ACE2 activity or expression have not been confirmed by others.…”
Section: Angiotensin-converting Enzymementioning
confidence: 75%
“…In regard to the benefits of an activated ACE2 pathway, several compounds have been identified that may act as allosteric activators of ACE2 including xanthenone (XNT) and diminazene aceturate (DIZE) to promote a higher ratio of Ang-(1-7) to Ang II [86]. Chronic treatment with DIZE ameliorated the extent of pulmonary hypertensin and fibrosis, renal tissue injury, and myocardial infarction consistent with enhanced levels of Ang-(1-7) and a reduction in Ang II [84,[87][88][89][90]. Interestingly, DIZE treatment was also associated with increased mRNA levels of ACE2 suggesting that DIZE may exhibit actions apart from the direct activation of the peptidase [87,91].…”
Section: Angiotensin-converting Enzymementioning
confidence: 99%